Character Education Through Inspirational Activities in the Nusantara Module Course in the Independent Student Exchange Program - Saragih, Alkausar; Batubara, Ismed; Ali, Rahmadi; Siregar, Bonanda Jafatani; Purba, Nelvitia (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2024)
Inspiration is one of the sub-discussions in implementing the Indonesian archipelago module in the independent student exchange program. This activity presents an inspiring figure from the area, whether a cultural figure, politician, official, or someone considered capable of inspiring students. This research aims to see what character education students receive during this activity. The sample for this research was 23 students participating in the second class of the 2022 independent student exchange program from several regions in Indonesia. This research method is qualitative descriptive research with data collection techniques through observation, interviews, and direct involvement in inspirational activities. In this inspirational activity, inviting a central figure who can provide insight, experiences, and tips so that this figure can be successful and become famous is very important as motivation and encouragement to the participants when they later achieve success in life. The character education obtained in this activity is the religious character, independence, tenacity, hard work, courage, discipline, never giving up, optimism, and cooperation.